2015
DOI: 10.1159/000439442
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer Specific Risk Score Is Associated with Postoperative Complications Following Open Ivor-Lewis Esophagectomy for Adenocarcinoma

Abstract: Background/Aims: Surgery for esophageal cancer is associated with a high morbidity and mortality. With this study, we investigated if a validated preoperative risk score correlates with overall morbidity, mortality, anastomotic insufficiency, respiratory complications and with the severity of complications after open Ivor-Lewis esophagectomy. Methods: A total of 94 patients undergoing esophageal resection for adenocarcinoma between 2005 and 2009 were included. Patients were assigned using the preoperative risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…This score was first described by Schroeder et al who demonstrated a correlation between the risk score and outcome of patients undergoing esophageal resection [16]. Our current results underline this hypothesis and are consistent with previous findings from our group for esophageal cancer surgery [25]. Also known as risk score for prediction of outcome following complex surgery is the POSSUM score, which was also considered in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This score was first described by Schroeder et al who demonstrated a correlation between the risk score and outcome of patients undergoing esophageal resection [16]. Our current results underline this hypothesis and are consistent with previous findings from our group for esophageal cancer surgery [25]. Also known as risk score for prediction of outcome following complex surgery is the POSSUM score, which was also considered in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Preoperative investigations included clinical examination, assessment of physical condition, American Society of Anesthesiologists physical status classification system (ASA-Score), Karnofsky-Index, body mass index, concomitant diseases (cardiac comorbidities such as hypertension, coronary heart disease, myocardial infarction in the past and pulmonary comorbidities as well as diabetes mellitus), weight loss during the last six months before surgery, consumption of alcohol and nicotine, blood tests including tumor markers, lung and cardiac function tests. The staging consisted of endoscopy with biopsy and histological examination, endosonography, and computed tomography of the thorax and abdomen as described previously [15].…”
Section: Data Collectionmentioning
confidence: 99%
“…Some scores share similar factors, like an increased risk with age, large tumor size, LN metastasis, inflammatory processes, malnutrition, and comorbidities [10, 11]. Some scores are based on physiological parameters, like the Portsmouth-Physiological and Operative Severity Score for mortality (P-Possum) score [12] and the National Cancer Database – Japan Risk Calculator (NCD) Surgery Risk Calculator, based on an extensive database from Japan.…”
Section: Introductionmentioning
confidence: 99%